Staff Development for networked learning: Learning from staff and students - Weedon, Elisabeth; Broumley, Liz; MacLean, Colleen (Proceedings of the International Conference on Networked Learning, 2002)
This study explores, through a case study the impact of both formal and informal staff development. It is suggested that the Kolb cycle and socials constructivist theory provides a useful starting point for exploring development drawing on data gathered in interviews, a focus group session which can then triangulated with data from other sources. However, it is also recognised the there may be a need for developing the Kolb cycle into a helix to account for reflection on experience which subsequently guides future action. Different types of staff development are then considered, distinguishing between formal and informal staff development. Finally issues arising out of these studies are identified and future areas for research suggested.